O processo de urbanização e o desenvolvimento geoeconômico da cidade de Medianeira - PR - Jacinto, Janério Manoel (2013)
This thesis is based on the study of small cities, with spatial area centered in the city of Medianeira, focusing its settling process, urbanization, geoeconomic questions as well as the (re)production of its urban space. The research portraits this city as a micro pole, exercising its centrality among other adjacent municipalities, its insertion in the urban web and also in the mesoregion of western Paraná. On the axis Cascavel - Foz do Iguaçu, Medianeira is an outstanding city when compared to other small cities in regard to its function and form, its goods and the services it offers to its population, and its integration to the regional context. The research analyses the city of Medianeira and aims at showing why it contrasts with the other cities on the axis, once its historical settling and urbanization process occurred next to theirs, in the end of 40's. It also highlights the importance of two cooperatives, Lar and Frimesa, of the Federal Technological University of Paraná, of the health area and of all the other companies which act in the production, trade and service sectors, being all of them important to urbanization and geoeconomic development in local and regional scale. It addresses the speculation and the occupation of irregular areas. Facing the (re)production of urban space, mainly in the horizontally form, and jobs demand, it becomes evident that public managers must take measures in relation to the infrastructure, mainly in inhabitance and transportation sectors.